The Ethical Compass: Guiding Auditor Choices in A Jakarta Public Accounting Firm - A.Fadli Mappisabbi; Steviani Batti; Nurasia Natsir (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The study examines the critical role of professional ethics in auditor decision-making, focusing on public accounting firms in Jakarta, Indonesia. Employing a convergent parallel design, the research integrates qualitative case study findings with quantitative survey results to provide a comprehensive understanding of the factors influencing ethical behavior in the auditing profession.The qualitative component explores the ethical dilemmas faced by auditors, drawing on Kohlberg's Theory of Moral Development, Rest's Four-Component Model, and the Theory of Planned Behavior. Through in-depth interviews and document analysis, the study reveals that auditors encounter complex ethical challenges stemming from client pressures, organizational incentives, and ambiguous professional guidelines. The findings highlight the pivotal role of ethical culture and leadership in shaping auditors' decision-making processes.The quantitative component complements the qualitative insights by surveying a larger sample of auditors across multiple firms. Descriptive and inferential analyses are conducted to assess the relationships between key variables, including organizational culture, professional guidelines, moral development, and ethical decision-making. The results provide empirical support for the qualitative findings, confirming the significant influence of organizational factors and individual moral reasoning on auditors' ethical behavior. The study offers practical recommendations for enhancing ethical practice in the auditing profession. These include implementing robust ethical training programs, fostering mentorship relationships, and aligning organizational incentives with ethical objectives. The research highlights the importance of cultivating a strong ethical culture within accounting firms and emphasizes the need for clear, unambiguous professional guidelines to support auditors in navigating ethical dilemmas.